Minimization of total harmonic distortion in neutral point clamped multilevel inverter using grey wolf optimizer - Fahmi Ahyar Izzaqi; Novie Ayub Windarko; Ony Asrarul Qudsi (Institute of Advanced Engineering and Science, 2022)
The inverter has been attracting researchers for their application in renewable energy. So far, multilevel inverter is considered as low distortion class, which produces multilevel output voltage imitating a pure sine waveform. However, the needs for free distortion of output voltage have been motivating to improve multilevel pulse width modulation PWM generation method. In this paper, the modified PWM technique is proposed to reduce the voltage total harmonics distortion (THD) of multilevel inverter. This modulation technique is then applied to control a single-phase threelevel neutral point clamped multilevel inverter (NPC-MLI). Grey wolf optimizer (GWO) algorithm is utilized to generate optimal amplitude and phase shift of modified reference signal. The GWO algorithm is then compared with other optimization algorithms such as differential evolution (DE), human psychology optimization (HPO), and particle swarm optimization (PSO) to evaluate their performance in harmonic minimization. The performance of the proposed work is validated through simulation and experimentation on a prototype. The results show that the modified PWM technique optimized with GWO can reduce THD on NPC-MLI output voltage.